2013
DOI: 10.1177/1098612x13497212
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic signs of acromegaly in 68 diabetic cats with hypersomatotropism

Abstract: In order to describe the signs of acromegaly in cats, a case-control study was done based on computed tomography (CT) scans of the heads of 68 cats with hypersomatotropism and 36 control cats. All cats with a diagnosis of hypersomatotropism had diabetes mellitus, serum insulin-like growth factor-1 >1000 ng/ml and a pituitary mass. Measurements of bones and soft tissues were done by two independent observers without knowledge of the diagnosis. Pituitary masses were identified in CT images of 64 (94%) cats with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…Additionally, on retrospective MRI assessment of the head features of cat 3, there was increased parietal bone thickness and increased distance between the lateral aspects of the zygomatic arches. These changes have been described in cats with hypersomatotropism …”
Section: Casementioning
confidence: 67%
“…Additionally, on retrospective MRI assessment of the head features of cat 3, there was increased parietal bone thickness and increased distance between the lateral aspects of the zygomatic arches. These changes have been described in cats with hypersomatotropism …”
Section: Casementioning
confidence: 67%
“…The masses had dorsoventral dimensions between 4.2-16 mm (median 6.1). In 2/68 cats masses were only identified by means of MRI and in the other 2 cats acidophilic hyperplasia was found at necropsy (Lamb et al 2014). The same study demonstrated that 66% of cats had values for facial bone measurements and 19% of cats values for soft tissue measurements outside the normal range.…”
Section: Diagnostic Imagingmentioning
confidence: 78%
“…The upper limit of IGF‐1 concentration quantitation was 2,000 ng/mL, and any result above this value was recorded as 2,000 ng/mL. Pituitary contrast‐enhanced computed tomography was performed as previously described and a pituitary dorsoventral height, measured by a board‐certified radiologist, > 4 mm was considered to be enlargement …”
Section: Methodsmentioning
confidence: 99%